2018
DOI: 10.1111/ejn.14174
|View full text |Cite
|
Sign up to set email alerts
|

Midfrontal theta transcranial alternating current stimulation modulates behavioural adjustment after error execution

Abstract: Cognitive control during conflict monitoring, error processing, and post‐error adjustment appear to be associated with the occurrence of midfrontal theta (MFϴ). While this association is supported by correlational EEG studies, much less is known about the possible causal link between MFϴ and error and conflict processing. In the present study, we aimed to explore the role of band‐specific effects in modulating the error system during a conflict resolution. In turn, we delivered transcranial alternating current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 77 publications
0
59
2
Order By: Relevance
“…For executive functions, most studies applied online stimulation with the goal of entrainment. Faster responseswere induced by theta-tACS during response inhibition [55,57,60] and by alpha-or beta-tACS during time estimation [59]. Additionally, individual alpha-peak-tACS increased mental rotation performance [58].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For executive functions, most studies applied online stimulation with the goal of entrainment. Faster responseswere induced by theta-tACS during response inhibition [55,57,60] and by alpha-or beta-tACS during time estimation [59]. Additionally, individual alpha-peak-tACS increased mental rotation performance [58].…”
Section: Discussionmentioning
confidence: 99%
“…Further, Laczó and colleagues [38] applied another spatial attention task. They tested the facilitatory or inhibitory effects of attention on contrast detection thresholds, while stimulating at different gamma frequencies (40,60,80 Hz). Only gamma-tACS at 60 Hz improved the participants' contrast detection performance compared with sham.…”
Section: Attentionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alpha (8-13Hz) synchronizations over fronto-central electrodes as markers of the performance monitoring system activity (Luu et al, 2004;Trujillo & Allen, 2007;Cavanagh et al, 2009;Cohen, 2011). A recent study showed that inducing Theta over FCz by means of transcranial alternating current stimulation (tACS) resulted in modulation in behavioural adjustment after error execution (Fusco et al, 2018). More recently, Theta and Alpha synchronizations have also been detected during the observation of motor errors performed by an embodied avatar seen from a first-person perspective Spinelli et al, 2017;Pezzetta et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…PES is associated with increased theta activity over the medial prefrontal cortex (mPFC) [3], and PES of OCD patients was shown to be mainly driven by abnormally slow PC RTs rather than a failure to slow down after errors [1]. Notably, a recent study [4] has demonstrated that acute theta transcranial alternating current stimulation over the mPFC of healthy volunteers induced short-term reductions of PES without compromising post-error accuracy (PEA) in the Flanker task. Given the notion that the effects of stimulation may accumulate over repeated sessions [5], it is plausible that multiple stimulation sessions of the mPFC may induce long-term modifications to cognitive functions associated with error monitoring [5].…”
Section: Dear Editormentioning
confidence: 99%